No he's not correct
<span>(3 – 6y2)(y2 + 2)
= 3(y2) -6(y2)(y2) - 6y2(2) </span>+ 3(2)<span>
= 3y2 -6y4 - 12y2 </span>+ 6 <span>
= -6y4 - 9y2 +6</span>
Answer:
(3,3)
Step-by-step explanation:
Using the midpoint formula:
![m=\left( \dfrac{6+0}{2},\dfrac{4+2}{2} \right)=\left( \dfrac{6}{2},\dfrac{6}{2} \right)=(3,3)](https://tex.z-dn.net/?f=m%3D%5Cleft%28%20%5Cdfrac%7B6%2B0%7D%7B2%7D%2C%5Cdfrac%7B4%2B2%7D%7B2%7D%20%5Cright%29%3D%5Cleft%28%20%5Cdfrac%7B6%7D%7B2%7D%2C%5Cdfrac%7B6%7D%7B2%7D%20%5Cright%29%3D%283%2C3%29)
Hope this helps!
Answer:
![\frac{31}{50}](https://tex.z-dn.net/?f=%5Cfrac%7B31%7D%7B50%7D)
Step-by-step explanation:
percentage of graduates with loan = 62%
total sample = 50
Number of student in the sample with student loan
= (percentage of graduates with loan) x (total sample)
= 62% x 50
= 31
Proportion of student in the sample with student loan = ![\frac{31}{50}](https://tex.z-dn.net/?f=%5Cfrac%7B31%7D%7B50%7D)
Step-by-step explanation:
A =nr²
=3.14 × (80/2)
=3.14 × 40
= 125.6yd²